Analisis Transformasi Komik “Attack On Titan” Menjadi Animasi Berdasarkan Alur Cerita, Karakter, dan Gaya Visual - Maria Ligouri, Eloena Ketsiya; Fuad, Ahmad (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Attack on Titan, a popular manga by Hajime Isayama, was successfully adapted into an animated series—a transformation from print to an audio-visual medium that significantly expanded its global reach and cultural impact. Utilizing a qualitative descriptive method, this study analyzes how the adaptation created a new experience by leveraging motion, camera angles, color grading, music, sound effects, and voice acting to build tension and emotion. Drawing on data from observation, literature reviews, and studio interviews, the research examines the creative process of the production team, with a particular focus on the animation team's role in transforming the comic's story into animation. The findings indicate that this adaptation successfully made the Attack on Titan story and its characters more vibrant, powerful, and emotional.